Essential hypertension: effect of an oral inhibitor of angiotensin-converting enzyme. - MacGregor, G A (1979)
Captopril, a specific oral inhibitor of angiotensin-converting enzyme, was given to 18 unselected patients with moderate essential hypertension. Mean blood pressure fell by 14.5% at the maximum dose given, and this fall was significantly correlated with the initial plasma renin activity. The main fall in blood pressure occurred two hours after the first dose of captopril. These results suggest that captopril effectively lowers blood pressure in patients with essential hypertension and that the renin-angiotensin aldosterone system may maintain blood pressure in essential hypertension. This does not necessarily imply that the renin-angiotensin system is the cause of the high blood pressure.